DAMPAK PRAKTIK GREEN ACCOUNTING DAN ENVIRONMENTAL, SOCIAL, AND DISCLOSURE (ESG) DISCLOSURE TERHADAP NILAI PERUSAHAAN: THE IMPACT OF GREEN ACCOUNTING AND ENVIRONMENTAL, SOCIAL, AND DISCLOSURE (ESG) DISCLOSURE ON FIRM VALUE - Vivy, Vivy; Hijriah, Amanah; Fahmi, Muhammad (Universitas Riau, 2024)
The environment is a contemporary issue that must be considered account because business operations and the environment are intertwined. Mining companies are highprofile companies with high sensitivity to the surrounding environment. Investor perceptions that depend not only on company profits, but also on the company's concern for its surroundings make companies have to consider non-financial impacts, such as environmental and social. Uncovering the relation between Green Accounting, ESG Discloure and firm value is the focus objective of this research study. This research study uses quantitative methods, while the linear regression method in the SPSS v25 program is also used. In this study, Green Accounting is measured using PROPER, GRI (Global Reporting Initiative) Standard is used to measure ESG disclosure, and Tobin's Q ratio is used to estimate firm value. Coal mining subsector companies listed on the stock exchange (IDX) in 2018 - 2022 were used as the population in this study, the sample was selected using purposive technique. The results of this study show that Green Accounting has no effect on firm value and ESG Disclosure has a negative effect on Firm Value.